ASPEK FISIOLOGIS DAN BIOKIMIAWI INFEKSI JAMUR PATOGEN TUMBUHAN - Abdul Gafur . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2003)
Physiological and biochemical aspects of plant fungal pathogen infections. Interaction between plants and pathogens is a major subject of interest in the field of contemporary plant pathology. Specificity of this kind of interaction is a very comprehensive phenomenon involving complicated mechanisms at different levels. Elucidation of this phenomenon including physiological and biochemical aspects is therefore an important task. From this point of view, enzymes play one of the most important roles in the infection process and pathogenesis. Our current understanding in this area is quite limited. A relatively limited number of enzymes have so far been studied in relation to the infection process and pathogenesis in plants. In this review, ivolvement of the enzymes, i. e. cutinases, esterases, hydrolases, lyases, cellulases, depolymerases and proteases, during the pathogenesis and their role in different stages of disease development is analyzed.